2018
DOI: 10.22159/ijpps.2018v10i7.24665
|View full text |Cite
|
Sign up to set email alerts
|

Development of Anti-Wrinkle Cream From Pueraria Candollei Var. Mirifica (Airy Shaw and Suvat.) Niyomdham, “Kwao Krua Kao” for Menopausal Women

Abstract: Objective: The aim of this study was to incorporate Peraria candollei var. mirifica extract into the cream, to evaluate the physical properties and to conduct the skin tests in participants.Methods: Pueraria candollei var. mirifica was extracted with 95% ethanol to obtain crude pueraria extract (PCM). Crude PCM was developed as an anti-wrinkle PCM cream (B) intended for menopausal women. PCM cream was evaluated for stability of pH and viscosity, primary skin irritation, wrinkle reduction and moisturizing as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Destabilization of the emulsion through hydrolysis occurred during storage at elevated temperatures [13]. These findings are in line with a previous study using an anti-wrinkle cream which demonstrated that higher temperatures resulted in increased viscosity [19]. As evidenced in this study, storing the emulsions at 4 °C, 28 °C, and 40 °C resulted in an acceptably stable pH at nearly 6.0, which is tolerable and gentle to the skin.…”
Section: Stability Of Prepared Creamsupporting
confidence: 91%
“…Destabilization of the emulsion through hydrolysis occurred during storage at elevated temperatures [13]. These findings are in line with a previous study using an anti-wrinkle cream which demonstrated that higher temperatures resulted in increased viscosity [19]. As evidenced in this study, storing the emulsions at 4 °C, 28 °C, and 40 °C resulted in an acceptably stable pH at nearly 6.0, which is tolerable and gentle to the skin.…”
Section: Stability Of Prepared Creamsupporting
confidence: 91%
“…White Kwao Krua contains chromene compounds, such as deoxymiroestrol, miroestrol, and isomiroestrol, exhibiting a distinctive estrogen-like molecular structure, and isoflavonoids, namely genistein, daidzein, and puerarin [3,16]. Additionally, it is employed for breast augmentation and esthetic enhancement purposes [17]. Consequently, it is distributed through herbal markets, drugstores, and online retail platforms in various forms, including tablets, capsules, cookies, creams, and gels.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoestrogens are a group of compounds derived from plants that have estrogen-like structures or can replace the function of estrogen in its bond either with estrogen receptors ([ERs]-dependent pathway) or not (ER-independent pathway) [7,8]. Besides being easy to obtain and having no side effects, the phytoestrogens are also reported to have activity for the treatment of estrogen deficiency [9][10][11], thereby providing an alternative treatment for potent osteoporosis [12].…”
Section: Introductionmentioning
confidence: 99%